USGS and social media user dialogue and sentiment during the 2018 eruption of Kīlauea Volcano, Hawai‘i - Goldman, Robert T.; McBride, Sara K.; Stovall, Wendy K.; Damby, David E. (Frontiers in Communication, 2024)
Responsive and empathic communication by scientists is critical for building trust and engagement with communities, which, in turn, promotes receptiveness toward authoritative hazard information during times of crisis. The 2018 eruption of Hawai'i's Kīlauea Volcano was the first volcanic crisis event in which communication via the U.S. Geological Survey (USGS) social media group, "USGS Volcanoes" played a major role in providing eruption information to publics. Providing a concrete assessment of the social media effort during the eruption is necessary for optimizing future social media hazard crisis communication. We present qualitative and quantitative analyses of USGS Volcanoes' Facebook posts and over 22,000 follow-on comments spanning the 2018 eruption. Our analyses reveal that, for the 16 posts with the highest user engagement, USGS Volcanoes and informed non-USGS users directly answered 73% of questions and directly corrected or called out inaccuracies in over 54% of comments containing misinformation. User sentiments were 66% positive on average per comment thread regarding eruption information, and user feedback toward USGS Volcanoes, USGS scientists, or the Hawaiian Volcano Observatory was 86% positive on average. Quantitative sentiment analysis reveals a 61% correlation between users' overall expressed sentiments and frequency of the word "thank," providing further evidence that social media engagement by USGS Volcanoes and informed users positively impacted collective user sentiment. Themes emerging from our qualitative thematic analysis illustrate how communication strategies employed by USGS Volcanoes successfully engaged and benefitted users, providing insights for communicating with publics on social media during crisis situations.